New Diterpenes from a Godavari Mangrove, Ceriops decandra - Wang, Hui; Li, Min-Yi; Satyanandamurty, Tirumani; Wu, Jun (Planta Medica, 2013)
Eleven new diterpenes, named decandrins A−K (1–11), including nine abietanes (1–9) and two podocarpanes (10–11), were isolated from the barks of an Indian mangrove, Ceriops decandra, collected in the mangrove swamp of Godavari estuary, Andhra Pradesh, together with four known abietanes. The structures of these compounds were established on the basis of spectroscopic data (new compounds) or comparison with data in the literature (known compounds). This is the first report of abietane and podocarpane diterpenoids from C. decandra.
Keywords: Ceriops decandra; Rhizophoraceae; mangrove; diterpene; abietane; podocarpane